Sự sống của dân quê/Nhị Linh -- Hà Nội ban đêm/Tràng Khanh, Việt Sinh -- Từ nhỏ đến lớn/Tứ Ly Tử -- Từ cao đến thấp -- Mười quả trứng vịt/Hoàng Uẩn -- Hai cái thái cực/Nhất Linh -- Nửa chừng xuân/Khái Hưng - Nguyễn, Xuân Mai (2017)
16 tr.